2013
DOI: 10.1007/s00018-013-1487-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bacteria on epigenetic gene control

Abstract: Cellular information is inherited by daughter cells through epigenetic routes in addition to genetic routes. Epigenetics, which is primarily mediated by inheritable DNA methylation and histone post-translational modifications, involves changes in the chromatin structure important for regulating gene expression. It is widely known that epigenetic control of gene expression plays an essential role in cell differentiation processes in vertebrates. Furthermore, because epigenetic changes can occur reversibly depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 70 publications
0
46
0
8
Order By: Relevance
“…Furthermore, as mentioned above, the TLR-4 function and expression are modulated not only by genetic variants and haplotypes [11,85,86] but also by environmental factors (such as diet [138][139][140][141], mite allergens [142], air pollution [143]), and their cross-interaction with microbiota [141], which may remain in a healthy state or show alterations (i.e. dysbiosis and consequent endotoxemia associated with age or obesity) [144,145]and consequent epigenetic changes [146,147]. Thus, many limitations and concerns emerge.…”
Section: Therapeutic Role Of Tlr-4 Pathway: From Experimental Data Tomentioning
confidence: 99%
“…Furthermore, as mentioned above, the TLR-4 function and expression are modulated not only by genetic variants and haplotypes [11,85,86] but also by environmental factors (such as diet [138][139][140][141], mite allergens [142], air pollution [143]), and their cross-interaction with microbiota [141], which may remain in a healthy state or show alterations (i.e. dysbiosis and consequent endotoxemia associated with age or obesity) [144,145]and consequent epigenetic changes [146,147]. Thus, many limitations and concerns emerge.…”
Section: Therapeutic Role Of Tlr-4 Pathway: From Experimental Data Tomentioning
confidence: 99%
“…Epigenetic control of gene expression during a pathogenic bacterial infection is another important element in the regulation of host cell death. A recent report showed that many enteric bacterial pathogens, such as Salmonella typhimurium (17,18), Helicobacter pylori (19), and the enteropathogenic Escherichia coli (EPEC) (20), affect a diverse set of epigenetic factors such as DNA methylation and histone modification to regulate the selective activation or silencing of specific host genes (21). Thus, studies regarding the process leading to pathogen-induced cell death are likely to be critical to uncovering the mechanisms of pathogenesis.…”
mentioning
confidence: 99%
“…Recent studies have shown that microbes affect a diverse set of epigenetic factors, including DNA methylation, histone modification, chromatin-associated complexes and non-coding RNAs, to alter chromatin structure and gene expression [76]. SCFAs have been reported to influence the epigenome; specifically, butyrate is recognised as a potent histone deacetylase inhibitor [66, 77].…”
Section: Mechanisms For Microbiome-induced Metabolic Disordersmentioning
confidence: 99%